SARS-CoV-2 neutralizing antibody bebtelovimab – a systematic scoping review and meta-analysis - Liew, Mabel Nyit Yi; Kua, Kok Pim; Lee, Shaun Wen Huey; Wong, Kon Ken (Frontiers in Immunology, 2023)
The COVID-19 pandemic is a major global public health crisis. More than 2 years into the pandemic, effective therapeutic options remain limited due to a rapid viral evolution. Stemming from the emergence of multiple variants, a number of monoclonal antibodies are no longer suitable for clinical use. This scoping review aimed to summarize the preclinical and clinical evidence for bebtelovimab in the treatment of newly emerging SAR-CoV-2 variants. We systematically searched five electronic databases (PubMed, CENTRAL, Embase, Global Health, and PsycINFO) from date of inception to September 30, 2022, for studies reporting on the effect of bebtelovimab in SARS-CoV-2 infection, using a combination of search terms around “bebtelovimab”, “LY-CoV1404”, “LY3853113”, and “coronavirus infection”. All citations were screened independently by two researchers. Data were extracted and thematically analyzed based on study design by adhering to stipulated scoping review approaches. 39 studies were included, of which 34 non-clinical studies were narratively synthesized and 5 clinical studies were meta-analyzed. The non-clinical studies revealed bebtelovimab not only potently neutralized wide-type SARS-CoV-2 and existing variants of concern such as B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), and B.1.617.2 (Delta), but also retained appreciable activity against Omicron lineages, including BA.2.75, BA.4, BA.4.6, and BA.5. Unlike other monoclonal antibodies, bebtelovimab was able to bind to epitope of the SARS-CoV-2 S protein by exploiting loop mobility or by minimizing side-chain interactions. Pooled analysis from clinical studies depicted that the rates of hospitalization, ICU admission, and death were similar between bebtelovimab and other COVID-19 therapies. Bebtelovimab was associated with a low incidence of treatment emergent adverse events. In conclusion, preclinical evidence suggests bebtelovimab to be a potential treatment for COVID-19 amidst viral evolution. Bebtelovimab has comparable efficacy to other COVID-19 therapies, without evident safety concerns.